Demonstrating Attachment‐Based Family Therapy for Transgender and Gender Diverse Youth with Suicidal Thoughts and Behavior: A Case Study. Issue 1 (27th May 2021) - Russon, Jody; Smithee, Lauren; Simpson, Samantha; Levy, Suzanne; Diamond, Guy
Abstract : Suicide is a growing public health issue among adolescents. While the majority of transgender and gender diverse (TGD) youth are healthy, many experience suicidal thoughts and behavior (STB). Due to discrimination and stigma, TGD youth attempt suicide at higher rates then heterosexual, cisgender and even cisgender, LGBQ youth. Despite this vulnerability to suicide, few treatments have been developed and tested for this population. One treatment, attachment‐based family therapy (ABFT) has been adapted to work with LGBQ youth and may be promising for TGD adolescents at risk for suicide. This article provides an overview of our ABFT modifications for TGD youth with thoughts of suicide. Specifically, we illustrate how treatment outcomes, in a single case study, relate to processes within clinical treatment tasks. The case study demonstrates the application of these ABFT modifications with a self‐identified, gender nonconforming adolescent (who had recently attempted suicide) and his caregivers. Treatment evaluation measures were collected over the course of 24 weeks to illustrate the youth's clinical progress. The youth's suicidal symptoms diminished markedly by the end of treatment. Further, the family reported an increased ability for problem solving and more open communication by treatment conclusion. Resumen: El suicidio es un problema de salud pública cada vez mayor entre los adolescentes. Si bien la mayoría de los jóvenes transgénero y de géneros diversos (TGD) son saludables, muchos tienen pensamientos y conductas suicidas. Debido a la discriminación y al estigma, los índices de intento de suicidio en los jóvenes TGD son más altos que en los jóvenes heterosexuales, cisgénero e incluso LGBQ cisgénero. A pesar de esta vulnerabilidad al suicidio, se han desarrollado y se han evaluado pocos tratamientos para esta población. Un tratamiento, la terapia familiar basada en el apego (TFBA), se ha adaptado para trabajar con jóvenes LGBQ y puede ser prometedor para adolescentes TGD en riesgo de suicidio. Este artículo ofrece un resumen de nuestras modificaciones a la TFBA para los jóvenes TGD con pensamientos de suicidio. Específicamente, ilustramos cómo los resultados del tratamiento, en un solo caso práctico, se relacionan con los procesos dentro de las tareas del tratamiento clínico. El caso práctico demuestra la aplicación de estas modificaciones de la TFBA con un adolescente que se identificó como de género no conforme (y que recientemente había intentado suicidarse) y sus cuidadores. Se recopilaron las valoraciones de una evaluación del tratamiento durante el transcurso de 24 semanas para ilustrar el avance clínico del joven. Los síntomas de suicidio del joven disminuyeron notablemente al final del tratamiento. Además, la familia informó una mayor capacidad para resolver problemas y una comunicación más abierta al concluir el tratamiento. 摘要: 自杀是青少年中一个日益严重的公共卫生问题。虽然大多数变性和性别多样化（TGD）的青少年是健康的，但许多人经历过有自杀的念头和有自杀行为（STB）出现的时候。由于歧视和感到被污名化，TGD青少年试图自杀的比例高于异性恋、双性恋，还有双性恋的LGBQ青少年。尽管这类人群很容易有自杀的可能性，但针对这一人群的治疗方法很少被开发和试验出来。有一种治疗方法，即基于依恋的家庭治疗（ABFT）已被应用于针对LGBQ青少年的治疗方法，并可能对有自杀风险的TGD青少年有帮助。本文概述了我们对有自杀想法的TGD青少年进行干预的ABFT的实践。具体来说，我们在一个单一的案例研究中，说明了治疗结果与临床治疗任务的过程之间的关系。该案例研究展示了这些ABFT调适之后的应用，对象是一个自我认同的、性别不一致的青少年（他最近曾试图自杀）和他的照顾者。在24周的时间里，治疗评估措施都被汇总，以说明该青少年的临床进展。在治疗结束时，该青少年的自杀症状明显减少了。此外，家庭报告说，在治疗结束时，其解决问题的能力有所提高，沟通也更加开放。